Reliability of retrospective assessment of the age of first menstruation - Żarów, Ryszard; Woronkowicz, Agnieszka; Spring, Barbara; Kowal, Małgorzata; Brudecki, Janusz (Anthropological Review, 2023)
The age of the first menstruation is one of the indicators for assessing the course of puberty. It is also a sensitive indicator of the economic situation of individual professional groups or societies, and the low average age of menarche is widely recognized as a marker of society’s well-being. The aim of the study was to analyse the reliability of the retrospective method of assessing the age at menarche by comparing the results to the age obtained from continuous research. Data regarding the age at menarche came from longitudinal somatic development and physical fitness studies conducted between 1976 and 2022. In 2022, 47 women were examined. In continuous studies, the prospective method was used in the assessment of the age of first menstruation while in the 2004 and 2022 studies a retrospective method was applied. Only in 4 out of 47 women the age of the first menstruation declared in 2004 and 2022 (the women were 32–34 and 50–52 years old, respectively) was consistent with the one found in continuous studies. In other cases, there was a discrepancy between the age found in continuous studies and self-reported in 2004 or 2022 or between the age stated in 2004 and 2022. Of those women who were present for the 2022 study, 36 had information about the age of first menstruation from continuous studies and the age of menarche in 2004 was given. For this sample the arithmetic mean and the standard deviation of the age at menarche were calculated. It was found that the retrospective method often used in the assessment of the age of the first menstruation is not fully reliable, as the average discrepancy in the assessment ranged from nearly 1 month (0.05 years) to over 2 months (0.19 years) compared to the prospective method. Women surveyed in 2004 determined the age of the first menstruation more accurately compared to statements obtained 18 years later from the same women. This study suggests that long-term memory (LTM) of a significant life event of every woman is unreliable, as indicated by the difference in the declared age of the first menstruation of women examined in 2004 and 2022, which, in individual cases, was up to 3, 4 or 5 years.